Gambaran Gangguan Tidur pada Pasien Pasca Stroke Iskemik - Alya Ramadhini; Yuliarni Syafrita; Russilawati Russilawati (Jurnal Ilmu Kesehatan Indonesia, 2021)
Background : Sleep disorder is common to be the complication in stroke patients and can be a risk factor for stroke. Sleep disorder in stroke patients decrease the quality of life. Objective : The purpose of this study was to find out the prevalence of sleep disorders in a post-ischemic stroke patient and the association between sleep disorders and stroke risk factors. Methods: A cross-sectional study was conducted on post-ischemic stroke at the neurology outpatient clinic of Ibnu Sina Islamic Hospital Padang. Information about stroke risk factors is obtained through patient data and guided questionnaires. Types of sleep disorders were assessed through the 2005 Specialized Center of Research Sleep Questionnaire. Results: We found out there were 57 post-ischemic stroke patients, in which 37 post-ischemic stroke patients (64.9%) had sleep disorder incidences, such as apnea, restless legs syndrome, insomnia, and narcolepsy (38.6%, 36.8%, 35.1%, and 15.8%; respectively). There was an association between age and insomnia (p = 0.034,CI = 95%). On the other hand, there was no association between other risk factors (gender, diabetes mellitus, dyslipidemia, heart disease, obesity, smoking, and alcohol consumption) and insomnia, apnea, narcolepsy, and restless legs syndrome. Conclusions : The conclusion of this study was more than half post-ischemic stroke patients have sleep disorder with the most common were apnea. There was an association between age and insomnia. Keywords: sleep disorder, apnea, ischemic stroke